1988
DOI: 10.2307/1590995
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Pathogenicity of Five Serotype 2 Infectious Bursal Disease Viruses in Chickens

Abstract: The pathogenic potential of five strains of serotype 2 infectious bursal disease virus (IBDV) for specific-pathogen-free chickens was examined. There were no gross or microscopic lesions in the inoculated chickens. Bursa-to-body-weight ratios of IBDV-infected chickens were not significantly different from those of uninfected controls. Virus-neutralizing antibodies to IBDV of serotype 2, but not serotype 1, were detected in infected chickens. This study indicated that the serotype 2 viruses examined were infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(77 citation statements)
references
References 7 publications
2
69
0
1
Order By: Relevance
“…The aetiologic agent is a bisegmented (segments A and B) double-stranded RNA Avibirnavirus. Classical serotype 1 infectious bursal disease virus (IBDV) strains have been of great concern to the poultry industry for a long time, while all known serotype 2 IBDV strains are avirulent for chickens (Ismail et al, 1988). In the late 1980s, classical serotype 1 IBDV evolved into variant forms, in the USA (Synder, 1990), or very virulent (vvIBDV) forms in Europe, Asia and other major parts of the world (van den Berg, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The aetiologic agent is a bisegmented (segments A and B) double-stranded RNA Avibirnavirus. Classical serotype 1 infectious bursal disease virus (IBDV) strains have been of great concern to the poultry industry for a long time, while all known serotype 2 IBDV strains are avirulent for chickens (Ismail et al, 1988). In the late 1980s, classical serotype 1 IBDV evolved into variant forms, in the USA (Synder, 1990), or very virulent (vvIBDV) forms in Europe, Asia and other major parts of the world (van den Berg, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is non-enveloped 60 nm diameter icosahedral particle (Özel and Gelderblom, 1985;Kibenge et al, 1988). Serotype I strains are pathogenic, with the target organ being bursa of Fabricius (BF), with markedly different virulence, while studies demonstrated that serotype II strains do not cause disease or protect against infection (McFerran et al, 1980;Jackwood et al, 1982;Ismail et al, 1988;Zierenberg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Two distinct serotypes of IBDV designated as serotypes 1 and 2, have been identified. Serotype-1 viruses were differing in virulence to chickens, whereas serotype-2 viruses, initially isolated from turkeys, were avirulent (Ismail et al, 1988). Based on virulence and antigenicity, serotype-1 viruses had been classified as attenuated, intermediate virulent, classical virulent, variant and very virulent (Van den Berg, 2000).…”
Section: Issn: 2319-7706 Volume 6 Number 12 (2017) Pp 2655-2668mentioning
confidence: 99%